Performance and blood lactate on Gjessing and Concept II rowing ergometers - Lormes, W.; Buckwitz, R.; Rehbein, H.; Steinacker, J. M. (International Journal of Sports Medicine, 1993)
The Gjessing (GE) and the wind resistance (Concept II, CII) rowing ergometers were compared in 11 trained subjects during incremental exercise. Maximum power was 255 (200-370) W on GE, but 294 (204-393) W in CII (median and range, p < 0.05). If power was directly measured by a strain gauge and a displacement transducer in the CII, a 5.1% (3.2%-7.8%) higher maximum performance was obtained (314 [223-413] W, p < 0.05). Maximum stroke rates were higher in GE (33 [27-37]/min) than in CII (29 [24-35]/min, NS). Blood lactate increased faster with work rate and lactic anaerobic threshold was therefore lower in GE. Blood lactate was higher for every heart rate for GE compared to CII. This suggests higher anaerobic effort in GE rowing.